2021
DOI: 10.3332/ecancer.2021.1184
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with primary glioblastoma in Chile: single centre series

Abstract: Background: Glioblastoma (GBM) is the most common and most aggressive primary malignant brain tumour. The standard of care is surgical resection, followed by radiotherapy with concurrent and adjuvant temozolomide. In Latin America, there is scarcity of information about the incidence of GBM and even less data regarding outcomes. In this study, we describe the clinicopathologic features, management and outcomes of GBM patients. Methods: We describe a single-centre multidisciplinary team experience in managing G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For instance, there needs to be more epidemiologic information. Most of the articles we found were from Brazil [12,18,23,24] and from Mexico [13,14,17,20,25,26] .We found some from Colombia [22], Argentina [27,28], and Chile [19,21]. Nonetheless, most Latin American countries still need to report their epidemiologic information on gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, there needs to be more epidemiologic information. Most of the articles we found were from Brazil [12,18,23,24] and from Mexico [13,14,17,20,25,26] .We found some from Colombia [22], Argentina [27,28], and Chile [19,21]. Nonetheless, most Latin American countries still need to report their epidemiologic information on gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…The Latino mean age of diagnosis found in this study was 6.1 years lower, for a mean age of 50.89 years, 95% CI (47.8-53.9), suggesting that gliomas occur considerably earlier in Latinos than in non-Hispanic whites and is crucial because it represents a health problem and an economic problem since it is affecting an economically active population [6,15]. Wegman-Ostrosky et al proposed three possible explanations for the younger age at diagnosis [17]: 1) differences in the Latin American population pyramid compared to those from the US, 2) environmental exposure, and 3) genetic factors, such as germline mutations in TP53, MSH2, MLH1, and MSH6 [18,19] Moreover, the reported incidence of glioblastoma increases signi cantly with age, with a median of 63 years. As stated in the CBTRUS, the median age varies by ethnicity, with non-Hispanic whites having a higher median age (64 years) than Hispanics (60 years) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Brazilian study showed that GB was the most common glioma in patients [52]. In Chile, a 2021 single-center study with 74 patients showed a median OS of 13.9 months [77].…”
Section: Latin Americamentioning
confidence: 98%